Pengembangan Media Electric Blood pada PembelajaranSistem Peredaran Darah Manusia untuk Siswa Kelas V Sekolah Dasar - , Fitriyani; , Dra. Ratnasari Diah Utami, M.Si., M.Pd (2017)
Abstract This research aims to: 1) knowing how the natural sciences learning activities in grade V elementary school during this time. 2) Knowing the Media Development on natural sciences of the human blood circulatory system, 3) knowing the feasibility of Electric Blood media on natural sciences of the human blood circulatory system in elementary school grade VThis type of research is development research, using the method of research and development (Research and Development / R & D). This study includes 8 stages, requirements analysis, design of media project, object collection of media project, media design, media creation, validation expert, design improvements, and product ratings. Media that have been developed validated by experts, is experts of natural sciences matter and instructional media expert. After repairs and validated by experts then carried out the assessment test product to the user, is students of grade V as many as 33 students and 2 teachers grade V. This research used data collection techniques of interview, observation, documentation, and questionnaire. Data analysis technique using quantitative and qualitative analysis.The results showed that 1) learning of natural sciences grade V in the elementary school have beenused only media visual images, 2) that produced the electric blood media based LED lamps,3) The results of the assessment of the eligibility level average media electric blood by 85% of incoming material in the category is very feasible, assessment of the media expert of 92% in the category of very decent, and the average user assessment by teachers and students amounted to 89.2% entered on categories is very decent Keywords: development, instructional media, electric blood,